American Greetings : an automation versus outsourcing dilemma - Nagy, Andrea R.; Lee, Gene; Swersey, Arthur J. ([London] : SAGE, 2016)
As part of an industry with generous profit margins and high barriers to entry, American Greetings had spent decades in a comfortable position. Beginning at the turn of the 20th century, it had helped to create a mass market for the greeting card and had presided over its growth into a multi-billion-dollar industry. This case examines the challenges facing American Greetings in the 21st century.
Originally Published in: Nagy, A. R., Lee, G., & Swersey, A. (2008). American Greetings: An Automation versus Outsourcing Dilemma. 08-010. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; American Greetings Corporation; Business logistics -- Case studies; Contracting out -- Case studies; Automation -- Case studies